Clinical presentation of congenital neck mass in children - Siddique, Mazharul Alam; Hossen, Mahbuba; Taous, Ahmmad; Salam, Kazi Shamimus; Siddiquee, Belayat Hossain; Tarafder, Kamrul Hasan (Bangladesh Journal of Otorhinolaryngology, 2012)
Background: Congenital neck mass is a very common problem in children in Otolaryngology & Head-Neck Surgery and Paediatric Surgery Department but data of our country is inadequate and there is lack of published study. This study will help to diagnose congenital neck masses, evaluate the success of surgical treatment in our country. Objective: To assess the frequency of congenital neck mass in children and to see the clinical presentation of different congenital neck mass. Study design: Cross sectional prospective study. Place of study: Department of Otolaryngology Head & Neck Surgery, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Dhaka Medical College Hospital (DMCH)l, Dhaka and Mymensingh Medical College Hospital (MMCH), Mymensingh. Methodology: Patients below the age of 18 years with congenital neck mass who presented to three tertiary level hospitals from January 2010 to December 2010 were included in this study. Total thirty six patients were purposively selected. Age, gender, types of swelling and location were examined, investigations were done. Data was analyzed with SPSS software and was presented in the form of tables, diagrams and pie charts. Results: 36 patients with different congenital neck swelling were examined. Out of 36 patients, thyroglossal cysts were commonest- 21(58.33%). Other congenital lesions were as follows: Branchial cyst 7(19.44), Lymphangioma 3(8.33%), Haemangioma 3(8.33%), Dermoid cyst 2(5.55%). Midline was most common location 21 (58.33%). Conclusion: Congenital neck masses constitute important differential diagnosis for neck masses. These masses constitute diagnostic and therapeutic challenges for many clinicians. Correct diagnosis, safe and complete surgical excision requires sound knowledge of the location and extent of these masses. DOI: http://dx.doi.org/10.3329/bjo.v18i1.10409 Bangladesh J Otorhinolaryngol 2012; 18(1): 16-22